Potential Management Development Of Batik Small-Medium Enterprise In Pilang Village, Sragen - Asri Laksmi Riani; Edi Kurniadi; Mohammad Cholil; Mohammad Amien Gunadi; Atmaji Atmaji; Agung Prabowo (Institut Seni Indonesia Denpasar, 2020)
The study was conducted in Batik Small-Medium Enterprise (Batik SMEs) in Pilang Village of Sragen Regency. Pilang village is one of the producers of Batik, it considerably contributes to the Batik market in Solo region. The study was aimed at finding out the condition and the potential of development through management comprising financial, human resource, marketing, and production management. The Descriptive quantitative method was employed, the respondents were ten SMEs Batik entrepreneurs. The study found that SMEs relied on traditional and limited financial management methods. It was also found that their marketing aspect had not adopted a modern marketing and promotion strategy. Their production has run well, however they face hindrances in product innovation and design with local characteristics. Then, human resource management also faced obstacles in on time delivery, creativity, and payment system.